Advances in bioimaging techniques for studying cellular mechanics - Tong, Ge; Du, Zhenchen (Molecular & cellular biomechanics, 2024)
Recent bioimaging advances have greatly aided cellular mechanics research. These advances have given researchers a new understanding of cell structure and function. Thus, these approaches have great optical coherence tomography (OCT) and temporal resolution, helping researchers understand previously inaccessible mechanical cell functions. The biggest drawback of all current techniques is their low resolutions, poor specificity, and inability to investigate cellular mechanics in complicated biological contexts in real-time. Introducing Cellular Mechanics using Bioimaging Techniques (CM-BT) will solve these difficulties. Combining advanced imaging modalities with unique computational methodologies, CM-BT may improve understanding of cellular mechanics. These methods improve resolution, specificity, and real-time performance. This technology uses super-resolution microscopy, fluorescence lifetime imaging, and machine learning-based image processing to reveal local mechanical properties and intercellular interactions. The results indicate that CM-BT improved temporal and spatial resolutions. This allowed researchers to view cellular dynamics with unparalleled precision and clarity before the inquiry. This technique also provides fresh information on mecha no transduction processes, including migration and mitosis, which increases understanding of cellular pathology.